Contaminação química e microbiológica na cadeia produtiva do pêssego: contribuição à análise de risco - Schneider, Evandro Pedro (2012)
Identifying contamination potential risk in the peach production system is necessary to the construction of critical consciousness about the topic, as well as to the improvement of problem control in the productive chain such as Integrated Production of Fruits. From this issue, it is proposed to identify and supervise the farmers profile, their current level of contamination and monitor the peach chain, related to the presence of pesticides residues and microbiological contamination, in order to identify the vulnerabilities and risk situations connected to the use of pesticides and microbiological contamination in the peach productive chain, in the region of Pelotas, RS. As work methodology it was applied questionnaires, blood collected from producers (biological analyze), sample of fruits and water were collected during two consecutives harvests (2010/11 and 2011/12) in 25 productive farms. According to the diagnosis made, the lower education, the use of badly calibrated equipments, added to the insufficient technical assistance, constitute vulnerabilities related to the inadequate use of pesticides. The water used in the rural properties presents not only microbiological but also pesticide contamination. According to the percentages of unacomplishment of Maximum Limits of Residues and the inadequate use of pesticides non-authorized to the culture, it is concluded that the peach fruits and preserving (85,7%), are not totally safe by pesticides residues, demanding actions of conscientization and supervising of peach system production.